Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I've been given an assignment. Almost done except the last two are tripping me up. They are as follows:

1) if $2x^2-x=2y^2-y$ then $x=y$

2) if $x^3+x=y^3+y$ then $x=y$

I imagine they use a similar tactic as they both involve powers, but I've tried factoring,completing the square, difference of squares and difference of cubes and nothing seems to help.

Any hints would be appreciated.

share|cite|improve this question
Is (2) correct as written, or should the righthand side be $y^3+y$? As written, it’s very easy, since it reduces to $x^3=y^3$, and the cubing function is one-to-one. – Brian M. Scott Jul 12 '12 at 1:21
Yes that is correct. My bad. I should also say that I can also show a counterexample, but these seem true to me – user979616 Jul 12 '12 at 1:40
If you move everything over to (say) the left-hand side of each equation, you can factor-out "$x-y$". If this factor can be presumed zero, then $x=y$. However, in each case, you have another factor that could be zero as well; you need to rule-out this possibility. What do your instructions tell you about $x$ and $y$? (For instance, are they integers?) [Ah, just saw your other comment] You can use these other factors to find counter-examples; just choose values that make them zero. – Blue Jul 12 '12 at 1:50
Isn't it true that if f(x) =f(y), then x=y? – jeff Jul 12 '12 at 3:59
@jeff: Consider $f$ the square function. We have $f(-2) = 4 = f(2)$, but $-2 \neq 2$. – Blue Jul 12 '12 at 4:19
up vote 3 down vote accepted

Question $1$: The equation is equivalent to $2x^2-2y^2=x-y$. The left-hand side factors as $2(x+y)(x-y)$. So our equation can be rewritten as $$2(x+y)(x-y)=x-y.$$ Thus any pair $(x,y)$ such that $x\ne y$ and $2(x+y)=1$ is a counterexample to the assertion that $x$ must be equal to $y$. This was pointed out by ncmathsadist.

Edit: It turns out that one is supposed to show that the only integer solutions have $x=y$. This follows from the above calculation, since $2(x+y)=1$ has no integer solutions.

Question $2$: We look at the question as amended. We can factor and rewrite the equation as $(x-y)(x^2+xy+y^2)=-(x-y)$. If $x\ne y$, we can cancel $x-y$, and obtain $x^2+xy+y^2=-1$.

But the equation $x^2+xy+y^2=-1$ has no real solutions, since $x^2+xy+y^2\ge 0$ for all real $x$ and $y$. One way to see this is to complete the square, getting $$x^2+xy+y^2=\left(x+\frac{y}{2}\right)^2+\frac{3}{4}y^2.$$ The right-hand side is clearly never negative for real $x$ and $y$. So it is true that the only solutions of the original equation have $x=y$.

share|cite|improve this answer
Ah for part 1 I got that far. But since x and y have to be integars, there are no such integars such that x+y=1/2. So am I right to conclude that x=y – user979616 Jul 12 '12 at 3:37
@user979616: Certainly the only integer solutions have $x=y$, since the equation $2(x+y)=1$ has no solution in integers. Your post made no mention that variables were restricted to be integers. – André Nicolas Jul 12 '12 at 3:41

On 1), what if $x = 1/2$ and $y = 0$?

What tools are you permitted to use? Is calculus involved?

share|cite|improve this answer

For (2), if $x^3+x=y^3+y$, then $x^3-y^3=y-x$. A standard factorization that you should learn (if you haven’t already) is $x^3-y^3=(x-y)(x^2+xy+y^2)$. If $x\ne y$, you can divide by $x-y$ to get


Now write $(1)$ as a quadratic in $y$:


Use the quadratic formula to solve this for $y$ in terms of $x$; if you do it right, you’ll see why this is impossible (i.e., why there are no real solutions), and you’ll be able to conclude that $x-y$ must have been $0$ in the first place.

share|cite|improve this answer

For 1) Observe that (I am assuming $x,y$ are real numbers):

\begin{align} 2x^2-x=2y^2-y\\ &\implies (2x^2-x)-2y^2+x=(2y^2-y)-2y^2+x\\ &\implies 2(x^2-y^2)=(x-y)\\ &\implies 2(x-y)(x+y)=(x-y)\\ &\implies 2(x-y)(x+y)-(x-y)=(x-y)-(x-y)=0\\ &\implies 2(x-y)(x+y)-(x-y)=0\\ &\implies (x-y)(2(x+y)-1)=0\\ &\implies (x-y)=0 \text{ or } 2(x+y)-1=0\\ \end{align} So, either $(x-y)=0$ or $2(x+y)-1=0.$ If $x-y=0$ then $x=y$ and we have our result. What if $2(x+y)-1=0$? Then there is a possiblity that $x\neq y.$ But if $x=y=1/4$ then $2(x+y)-1=2(1/4+1/4)-1=2(1/2)-1=1-1=0.$ Thus in either case $x=y$ is a solution. Like ncmathsadist pointed out $x=1/2$ and $y=0$ also works but that doesn't mean that $x=y$ doesn't work! I think for precalculus level this is enough.

For 2) do a similar analysis and Brian has done enough for you in his answer.

share|cite|improve this answer

For 2), $f'(x) = 3x^2 + 1 > 0$, so $f(x) = x^3 + x$ is strictly increasing on $\mathbb{R}$, and is therefore injective.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.